2018
DOI: 10.1177/0886260518760610
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Children in Afghanistan: Community Perspectives

Abstract: Violence against children (VAC) is a significant international problem and, in Afghanistan, is particularly complex given the country has suffered armed conflict and extreme poverty for more than 30 years. The aim of this study was to examine the level of knowledge and observation of VAC by community leaders, professional groups, and business owners in three Afghan districts. A survey of community and religious leaders; health, socio-legal, and education professionals; and business owners from Kabul, Jalalabad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…The overall lack of ‘readiness’ (Almuneef et al, 2014) of society was demonstrated through examples of denial of abuse, taboos, fear of challenging predominant beliefs (Cameron et al, 2018), family structure – namely polygamy, and the perceived role of women (Afshar, 2016). These effects were evident throughout the reporting, assessment and intervention process, continuously hindering practitioners’ attempts to engage with families in order to protect vulnerable children and women.…”
Section: Discussionmentioning
confidence: 99%
“…The overall lack of ‘readiness’ (Almuneef et al, 2014) of society was demonstrated through examples of denial of abuse, taboos, fear of challenging predominant beliefs (Cameron et al, 2018), family structure – namely polygamy, and the perceived role of women (Afshar, 2016). These effects were evident throughout the reporting, assessment and intervention process, continuously hindering practitioners’ attempts to engage with families in order to protect vulnerable children and women.…”
Section: Discussionmentioning
confidence: 99%
“…Öğrencilerin %57.3'ü anne ve babasının çocuk yetiştirme tutumunu "koruyucu" olarak nitelemektedir (Tablo 1). etmeye çalışan ebeveynler çocuklarını ihmal edebilmekte ve böylece örselenme meydana gelebilmektedir (Altıparmak et al, 2013;Cameron et al, 2018;Guedes, Bott, Garcia-Moreno, & Colombini, 2016;Sarı, Ardahan, & Öztornacı, 2016;Taşar, Özcan, & Saç, 2018). 150 üniversite öğrencisi ile yapılan bir çalışmada, ailesi alt gelir düzeyinde olan öğrencilerin duygusal ve toplam örselenme ölçek puanları anlamlı derecede yüksek olduğu belirtilmiştir (Zeren et al, 2013).…”
Section: Bulgularunclassified
“…Bu nedenle anne ve baba eğitim durumu da çocukların örselenme ve yakın ilişkilerdeki yaşantıları üzerinde etkilidir. (Altıparmak et al, 2013;Cameron et al, 2018;Pekdoğan, 2016). Bu araştırmada eğitim düzeyi düşük olan babaların çocuklarının daha fazla örselenme ve yakın ilişkilerde daha çok sıkıntı yaşadığı belirlenmiştir.…”
Section: Bulgularunclassified
“…This is presented in Figure 1 Meeting basic physical (water, food, shelter, sanitation) and emotional needs, ensuring physical and emotional safety, removal from conflict, clear guidelines to staff and residents on child protection and domestic violence, child protection training, adherence to national and international legislation, child-centred approaches -e.g. no punishment, child-friendly and nurturing environments, multi-purpose spaces, opportunities for engagement; and tackling stigma and negative attitudes on vulnerability such as being in care, gender, violence, or mental health (Hutchinson et al, 2015;Cameron et al, 2018). School as a central hub in the support system, emotional literacy, principles of whole school ethos, integration of family-school-community approaches, teacher and community worker/volunteer training on problem recognition and strategies, sports and creative activities within a resilience framework, peer support, mentorship, or life skills training (Jordans et al, 2010;Baum et al, 2013;Hussein and Vostanis, 2013;Mutiso et al, 2017).…”
Section: Development Of Child Psychosocial Frameworkmentioning
confidence: 99%
“…It meets basic physical (water, food, shelter and sanitation) and emotional needs, ensures physical and emotional safety, removal from conflict, clear guidelines to staff and residents on child protection and domestic violence, child protection training, adherence to national and international legislation, child-centred approaches, e.g. no punishment, child-friendly and nurturing environments, multi-purpose spaces, opportunities for engagement; and tackling stigma and negative attitudes on vulnerability such as being in care, gender, violence or mental health (Hutchinson et al, 2015;Cameron et al, 2018). (Betancourt et al, 2017;Eruyar, Maltby and Vostanis, 2018;Howe et al, 2017).…”
Section: Development Of Child Psychosocial Frameworkmentioning
confidence: 99%